2013
DOI: 10.4103/1119-3077.116905
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric HIV in Kano, Nigeria

Abstract: Early diagnosis of pediatric HIV and prompt institution of treatment in children would go a long way in reducing the scourge of the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 18 publications
2
10
1
Order By: Relevance
“…The 7.57% overall incidence of mother-to-child transmission in this study is similar to several other findings within and outside of Nigeria [8,34] where mother-baby pairs received some form of antiretroviral therapy or prophylaxis for the prevention of mother-to-child transmission. While, our prevalence rate is higher than what was reported by Anoje et al [35], [36] and [37]; it is lower than the findings of Buseri and Okonkwo, Oyesakin et al and Anoje et al [33,38,39]. In spite of this, our current rate is a far cry from the desired zero to less than 1% advocated for good PMTCT outcome worldwide.…”
Section: Resultscontrasting
confidence: 70%
“…The 7.57% overall incidence of mother-to-child transmission in this study is similar to several other findings within and outside of Nigeria [8,34] where mother-baby pairs received some form of antiretroviral therapy or prophylaxis for the prevention of mother-to-child transmission. While, our prevalence rate is higher than what was reported by Anoje et al [35], [36] and [37]; it is lower than the findings of Buseri and Okonkwo, Oyesakin et al and Anoje et al [33,38,39]. In spite of this, our current rate is a far cry from the desired zero to less than 1% advocated for good PMTCT outcome worldwide.…”
Section: Resultscontrasting
confidence: 70%
“…7 Paediatric inpatient programmes were the most common context (17), 6,7,10,[13][14][15][16][17][18][19][21][22][23][24][25]29,30 followed by nutrition centres (four), 9,11,12,27 EPI centres (three), 20 programmes (three). 8,20,31 The assessment for quality showed that most of the included studies (20) [9][10][11][12][15][16][17][18][19][20][22][23][24][25][26][27][28][29][30][31] were of fair or good quality and the remainder (six) [6][7][8]13,…”
Section: Resultsmentioning
confidence: 99%
“…9,23,28,31 Paediatric HIV prevalence across contexts in southern and eastern Africa was 17·8% (95% CI 12·8-22·7) and prevalence in west and central Africa was 9·8% (95% CI 4·2-15·3). Because of the small numbers of studies from Asia and Oceania, these geographical settings were not included in stratifi ed analyses.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Predominant presentations include respiratory infections, malnutrition, diarrhea, and septicemia [13] . Fever and persistent generalized lymphadenopathy were common symptom and sign at presentation in our study.…”
Section: Discussionmentioning
confidence: 99%